Sifat Antagonistik Lactobacillus sp B441 dan II442 Asal Tempoyak terhadap Staphylococcus aureus - Tri Wardani Widowati; Basuni Hamzah; Agus Wijaya; Rindit Pambayun (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2014)
Lactobacillus sp B441 and II442 were species of lactic acid bacteria isolated from tempoyak, a kind of food fermented made from durian flesh. Staphylococcus aureus is a pathogenic bacteria that has natural habitat on the surface of human body such as on the skin and in mucous membranes like the nose. Contamination of Staphylococcus aureus was a risk factor in tempoyak fermentation, especially, during taking the durian flesh from seeds. The aim of this research was to observe antagonistic property of Lactobacillus sp B441 and II442 isolated from tempoyak during low temperature fermentation against Staphylococcus aureus. Phenotypic identification using API 50 CHL test kit indicated that isolates were Lactobacullus plantarum B441 and Lactobacillus plantarum II442. Based on co-culture analysis show that isolates of Lactobacillus plantarum B441 and II442 have bactericidal effect against Staphylococcus aureus ATCC 25923 as a indicator of pathogenic bacteria. At 25 th hours, population of Staphylococcus aureus ATCC 25923 in mix-culture with Lactobacillus plantarum B441 and Lactobacillus plantarum II442 decreased 3 – 4 log cycle from initial population. However, population of Staphylococcus aureus ATCC 25923 in mono-culture increased 2 log cycles at 25 th hours. ABSTRAKLactobacillus sp B441 dan II442 merupakan spesies bakteri asam laktat yang diisolasi dari tempoyak yaitu makanan fermentasi dari daging buah durian. Staphylococcus aureus adalah bakteri patogenik yang habitat alaminya pada permukaan kulit manusia dan membran mukosa seperti hidung. Proses fermentasi tempoyak khususnya saat pemisahan daging buah durian dari bijinya beresiko terkontaminasi oleh Staphylococcus aureus. Tujuan dari penelitian ini adalah mengkaji sifat antagonistik dari Lactobacillus sp B441 and II442 yang diisolasi dari tempoyak terhadap Staphylococcus aureus. Identifikasi secara fenotif menggunakan API 50 CHL test kit menunjukkan bahwa isolat bakteri asam laktat tersebut adalah Lactobacullus plantarum B441 dan Lactobacillus plantarum II442. Berdasar uji co-culture diketahui bahwa kedua spesies tersebut mempunyai efek bakterisidal terhadap bakteri Staphylococcus aureus ATCC 25923. Pada jam ke 25 Staphylococcus aureus yang ditumbuhkan secara mix-culture dengan Lactobacillus plantarum B441 dan Lactobacillus plantarum II442 asal tempoyak turun 3 – 4 log cycle dari populasi awal. Sedangkan populasi Staphylococcus aureus ATCC 25923 secara mono-culture meningkat sekitar 2 log cycle pada jam ke 25.